Pneumoperitoneum: A rare life threatening complication post ERCP! - Iqbal, Arham; Anis, Muhammad Wajeeh; Younus, Mohammad Ijlal (Journal of the Pakistan Medical Association, 2022)
Respected Editor, Endoscopic Retrograde Cholangiopancreatography (ERCP) is an invasive medical procedure commonly used to identify and treat biliary system and pancreatic disorders. It is the combination of both endoscopic and radiologic imaging techniques that, although widely used, and usually a safe procedure, it can rarely lead to life threatening complications including but not limited to pancreatitis, cholangitis, hemorrhage and perforation leading to pneumoperitoneum. The occurrence of free air in the peritoneal cavity post-ERCP is a rare event (< 1%), which is usually the result of duodenal or ductal perforation related to therapeutic ERCP with sphincterotomy.[1] Our discussion is based on the incidence of pneumoperitoneum occurring in patients post ERCP. According to a case report, a 29- year- old female was diagnosed with postpartum jaundice and biliary stones. Consequently, she was investigated using ERCP and treated with biliary stenting and bile flow restoration. Post ERCP, the patient developed severe epigastric pain radiating to the right shoulder and x-ray revealed air under the diaphragm, i.e. pneumoperitoneum.[2] In another report, a 72 year old woman who underwent ERCP to treat biliary stricture and provide stenting was found to have pneumobilia and pneumoperitoneum due to rupture of intrahepatic bile ducts during ERCP.[3] Another case has been reported with the same issue in which an 84 year old known case of pancreatic carcinoma with hepatic and lung metastasis underwent multiple ERCPs due to obstructive jaundice, performed an urgent CT scan, the very next day, which showed the presence of free air in the peritoneal cavity.[4] Therefore, in light of the cases mentioned above-, physicians should be mindful of this rare, life- threatening complication of ERCP and take great care and warn the patient before performing the procedure. A useful strategy to combat this complication, a nasogastric tube for bowel decompression immediately after ERCP can greatly reduce the chances of developing a pneumoperitoneum.